Interpreters as Historians in China - Lung, Rachel; Li, Donghui (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractSubsequent to the western effort in researching the history of interpreting, Chinese scholars have also shown initial interest in the subject. Since China has always valued the recording of history, it seems that historical resources would offer the data required for such an investigation. Interestingly, some historical data relating to interpreting events seem to display a regular linguistic device: the use of dialogues to document exchanges between Chinese and foreign envoys. According to Li Nanqiu (2002), this observation suggests that interpreters’ words were put down in writing as part of historical records. Such a claim, however, is not entirely conclusive. Based on examples drawn from primary historical records, this article analyzes discourse features of historical records of interpreting events, and shows the possible role of interpreters as historians, or consultants, in the recording of history in the early diplomatic history of China.